SSI-Based WebQuest: Instructional Media for Improving Critical Thinking Skills of Alpha Generation in Science - Laudia, Stefanie Marla; Widodo, Wahono; Sudibyo, Elok; Hendratmoko, Ahmad Fauzi; Obra Jr, Mario R (Jurnal Inovasi Pendidikan IPA, 2025)
Critical thinking is essential for today's students (Alpha Generation) due to rapid technology and globalization. It means thinking logically and making wise decisions. This research aimed to create an SSI-based WebQuest to improve critical thinking in elementary science students. This tool was designed using the ADDIE model and tested on 20 Grade V students at an international Christian school in West Surabaya during the second semester of 2023/2024. The research design used a one-group pretest-post-test approach. Data were collected through multiple methods, including validation, observation, a critical thinking skills test, and a questionnaire. The data were analyzed using descriptive and quantitative methods. Students' critical thinking skills were examined by n-gain and nonparametric tests. The results showed that (1) the developed media was classified as very valid, (2) learning activities were carried out very well, (3) students' critical thinking skills increased with an average n-gain value of 0.70 (high category), and (4) students' response to the learning that was carried out was classified as good with a percentage of 81%. The developed science learning materials are valid, practical, and effective in improving critical thinking among young students (Generation Alpha). This study highlights the value of using real-world socio-scientific issues in science education to help students understand the links between science, technology, and society. The findings offer a basis for future research on creating effective learning tools to enhance critical thinking across subjects and can inform teacher training in designing and using WebQuest-based materials centered on these real-world issues.